Total synthesis of cytotoxic sponge alkaloids Motuporamines A and B - Baldwin, J; Vollmer, H; Lee, V (1999)
The synthesis of two sponge alkaloids, Motuporamines A and B is reported. The key step involved a reductive amination using sodium triacetoxyborohydride.